Development of interactive maths teaching tool for engineering education / Saiyed Rasol Tuan Muda - Saiyed Rasol , Tuan Muda (2019)
This research and development work is to develop interactive math teaching tool for engineering education which can be used as an interest inculcating tool among secondary school students towards mathematics and encouraging them to embark on engineering study. The objective is to develop an initial set of math software that can be used as basis for continuous development to realize a locally developed tool as an alternative to existing software that are used today. The agenda is to minimize dependency on foreign tool in engineering education teaching, learning and research. The approach used is teaching and learning strategy that employs technology that relates subjects to application in reality with simple clear and attractive examples. A number of basic interactive math functions are built together with examples application in telecommunication and mechanical and automotive engineering which form the norm of every human daily life examples. This work has indicated that an interactive math software imbedded with more than 25 math functions can be gradually developed and further improved by encouraging graduate students to be engaged in engineering math research and development work. This work can be orchestrated with a novel objective of ultimately the country does not be too much dependent on foreign software at primary, secondary and tertiary math education. The results of this work can be used as basis to do more research for better improvement. This bits of work has undergone two field trial exercises via 2 Interactive Math for Engineering Workshops and the feedback from 33 participating students at forms 3,4 and 5 levels are very encouraging. On average 16 out of 25 or 64 % of the topics derived from the software have ratings of good to excellent. On the overall rating, 21 out of 33 or about 64 % of the students voted the software to be between good to excellent.